Predictors of cancer‐specific mortality after disease recurrence following radical cystectomy. (3rd September 2012) - Rink, Michael; Lee, Daniel J.; Kent, Matthew; Xylinas, Evanguelos; Fritsche, Hans‐Martin; Babjuk, Marko; Brisuda, Antonin; Hansen, Jens; Green, David A.; Aziz, Atiqullah; Cha, Eugene K.; Novara, Giacomo; et al.
Abstract : Study Type – Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? Outcomes after disease recurrence in patients with urothelial carcinoma of the bladder treated with radical cystectomy are variable, but the majority of patients die from the disease within 2 years after disease recurrence. Knowledge about prognostic factors that may influence survival after disease recurrence is limited. We found that outcomes after disease recurrence in patients with urothelial carcinoma of the bladder are significantly affected by common clinicopathological factors. In addition, a shorter time from surgery to disease recurrence is significantly associated with poor outcomes. These factors should be considered when scheduling salvage chemotherapy protocols/clinical trials. OBJECTIVE: To describe the natural history following disease recurrence after radical cystectomy (RC) and to identify prognostic factors that influence cancer‐specific survival with special focus on time from RC to disease recurrence. METHODS: We identified 1545 patients from 16 international institutions who experienced disease recurrence after RC and bilateral lymphadenectomy. None of the patients received preoperative chemotherapy; 549 patients received adjuvant chemotherapy. A multivariable Cox regression model addressed time to cancer‐specific mortality after disease recurrence. RESULTS: The median cancer‐specific survival time after disease recurrence was 6.9 months (95% CI 6.3–7.4). Overall, 1254 of 1545 patients died from urothelial carcinoma of the bladder and 47 patients died from other causes. The actuarial cancer‐specific survival estimate at 12 months after disease recurrence was 32%. On multivariable analysis, non‐organ‐confined tumour stages (hazard ratio [HR] 1.38, P = 0.002), lymph node metastasis (HR 1.25, P < 0.001), positive soft tissue surgical margin (HR 1.32, P = 0.002), female gender (HR 1.21, P = 0.003), advanced age (HR 1.16, P < 0.001) and a shorter interval from surgery to disease recurrence ( P < 0.001) were significantly associated with cancer‐specific mortality. The adjusted risk of death from cancer within 1 year after disease recurrence for patients who recurred 6, 12 and 24 months after surgery was 70%, 64% and 60%, respectively. CONCLUSIONS: Over two‐thirds of patients who experience disease recurrence of urothelial carcinoma of the bladder after RC die within 12 months. Common clinicopathological factors are strongly associated with cancer‐specific mortality. A shorter time from surgery to disease recurrence is significantly associated with poor outcomes. Accurate risk stratification could help in patient counselling and decision‐making regarding salvage treatment.